BAY LEAF IN DYSLIPIDEMIA THERAPY - EKANANDA A.R, NARITA (Majority, 2015)
Abstract Dyslipidemia is a disorder of lipid metabolism defined as elevated total cholesterol , Low Density Lipropotein (LDL) cholesterol serum, triglycerides level and low levels of High Density Lipoprotein (HDL) cholesterol serum. Control of dyslipidemia can be done with control diet and the consumption of drug. Bay leaf is one of traditional drug that can decrease total cholesterol , LDL, triglycerides level and increase HDL cholesterol serum level. Bay leaf contains some active regiments such as flavonoid, quercetin and niacin that can be effected to total cholesterol, LDL, triglycerides and HDL level. Keywords: bay leaf, dyslipidemia, HDL, LDL, total cholesterol, triglycerides Abstrak Dislipidemia merupakan gangguan metabolisme lipid berupa peningkatan kadar kolesterol total, kolesteroll Low Density Lipoprotein (LDL), trigliserida darah, dan penurunan kolesterol High Density Lipoprotein (HDL). Pengontrolan dislipidemia dapat dilakukan dengan pengontrolan pola makan dan konsumsi obat. Daun salam merupakan salah satu obat tradisional yang dapat menurunkan kadar kolesterol total, kolesterol LDL, trigliserida darah dan meningkatkan kolesterol HDL. Beberapa kandungan pada daun salam seperti flavonoid, kuersetin dan vitamin B3 (niasin) dapat berefek pada kadar kolesterol total, kolesterol LDL, HDL dan trigliserida darah. Kata kunci: daun salam, dislipidemia, HDL, kolesterol total, LDL, trigliserida